Development of work redesign for the achievement of the company's strategic goals - Gusti Adriansyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This research aims to develop a work redesign at PT Astra Gemilang Abadi (PT AGA) in Sidoarjo to address the gap between the company’s strategic goals and daily operations. The main issue examined is how unclear job descriptions affect employee performance and organizational efficiency. The study explores how job redesign can align individual tasks with PT AGA's vision, mission, and strategic goals. A descriptive quantitative approach, utilizing job characteristics theory and the RACI matrix, was used to analyze and redesign job descriptions for key positions. Data were collected through questionnaires, interviews, and observations to assess the effectiveness of the redesign. The findings indicate that a structured and relevant job design, coupled with improved internal communication, can enhance employee motivation, increase operational efficiency, and reduce turnover rates. Furthermore, involving employees in the redesign process positively impacts job satisfaction and engagement. The redesign focused on operational staff and management, ensuring their tasks were better aligned with the company’s strategic objectives. This research contributes to human resource development by extending job characteristics theory and offering practical insights into how job redesign can improve organizational performance. The study emphasizes the importance of clear, measurable performance indicators to support productivity and long-term growth.